Selection of radio transmitter and attachment method for post-release monitoring of captive-bred reintroduced Red-billed Curassow Crax blumenbachii, Brazil - Bernardo, Christine Steiner S. [UNESP]; Cresswell, Brian; Lloyd, Huw; Azeredo, Roberto; Simpson, James (Springer, 2011)
Long-term monitoring of reintroduced individuals is a central component of many endangered species reintroduction programs. Radio-telemetry techniques are rarely used to monitor reintroduced captive-bred Cracids and few data exist regarding possible adverse effects of radio-tagging Cracids. In this study, we identify an appropriate radio transmitter design and develop a suitable attachment method that minimizes anthropogenic influence and enables long-term, post-release monitoring (2-3 years) of reintroduced captive-bred Red-billed Curassows in the Brazilian Atlantic Rainforest. We also review studies about the effects of different VHF radio transmitter models on survival, reproduction, behavior, and physiology of Galliformes.
Keywords: Radio-telemetry; radio transmitters; reintroduction; Cracids; Atlantic rainforest